Organic ammonium salt modified perovskite thin film, perovskite solar cell and preparation
By introducing large-size organic ammonium salt compounds into the perovskite precursor, the [PbI6]4-octahedral framework is stabilized, and the problem of poor stability of perovskite solar cells is solved, and the photoelectric conversion efficiency and stability are significantly improved.
Patent Information
- Application Number
- CN202311402171.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The stability of perovskite solar cells is poor, mainly because the size of A-position cations does not match other elements, resulting in low lattice energy and is susceptible to water, oxygen and ultraviolet rays, resulting in degradation.
Large-size A-position cationic ammonium salt compounds are introduced into the perovskite precursor PbI2 solution to stabilize the [PbI6]4-octahedral frame, reduce internal defects and grain boundaries of the film, and thus improve the quality of the perovskite film.
It significantly improves the stability and photoelectric conversion efficiency of perovskite solar cells, improves grain size and crystallinity, reduces defects and grain boundaries, and enhances the separation and transmission of carriers.
Smart Images

Figure CN119907394A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of perovskite solar cells, and in particular relates to a perovskite film modified by an organic ammonium salt, a perovskite solar cell containing the perovskite film modified by the organic ammonium salt, and a preparation method thereof. Background Art
[0002] In recent years, the photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has increased rapidly, with the highest efficiency reaching 26%, which is comparable to commercial silicon-based solar cells.
[0003] Compared with commonly used silicon crystal materials, perovskite films have the characteristics of abundant raw materials, simple preparation process, high extinction coefficient, flexibility and cost advantage, so they have become a hot topic of concern in the scientific and business communities. However, compared with silicon crystal solar cells, the stability of perovskite solar cells is still a bottleneck problem in their development. An important reason for its poor stability is that the size of the A-site cation does not match that of other elements, resulting in low lattice energy of the crystal, which is easily corroded by water, oxygen and ultraviolet rays and degraded.
[0004] Regulating the size of A-site cations is an effective way to increase the lattice energy of perovskites, enhance material stability and inhibit the decomposition of perovskites. The introduction of A-site cations of appropriate size can not only improve the crystallization energy of perovskites, but also reduce the generation of defects, reduce the recombination probability of carriers, inhibit the hysteresis of the current density-voltage curve, and further improve the photoelectric conversion efficiency of the corresponding battery. Summary of the invention
[0005] The present invention introduces a large-sized A-position cationic ammonium salt compound into the perovskite precursor PbI2 solution to stabilize [PbI6] 4- The octahedral framework reduces internal defects and grain boundaries in the film to improve the quality of the perovskite film, thereby significantly improving the stability and photoelectric conversion efficiency of perovskite solar cells.
[0006] One of the purposes of the present invention is to provide an organic ammonium salt modified perovskite film comprising [PbI6] stabilized by organic ammonium cations 4- Structure, the organic ammonium cation is RNH3 + or R1R2R3(NH2) n + The invention relates to an organic ammonium cation with a large radius, R is an alkyl chain having 1 to 3 atoms, R1, R2, and R3 are independently alkyl chains having 1 to 3 atoms, and n is an integer of 1 to 3.
[0007] According to the present invention, the radius of the organic ammonium cation is greater than 250 pm, preferably 250 to 400 pm; the organic ammonium cation is selected from CH3NH3+ (methylamino), CH3CH2NH3 + (ethylamino), CH(NH2)2 + (Carbamimidyl), CH3C(NH2)2 + (acetamimidyl), C(NH2)3 + (Guanidyl), (CH3)2NH2 + (dimethylammonium salt).
[0008] According to the present invention, in the perovskite film, the organic ammonium cation is [PbI6] 4- 0.005-20wt% (by mass percentage), for example, it can be any value or any range between two values in 0.005, 0.01, 0.02, 0.05, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20wt%. Preferably, the organic ammonium cation is [PbI6] 4- 0.01~5wt%.
[0009] In the process of preparing the perovskite active layer, the present invention adds an organic ammonium salt compound with a relatively large cation to the PbI2 solution, and introduces the large-sized organic ammonium salt compound into the perovskite precursor, so that in the perovskite APbI3 structure, the organic ammonium salt cation replaces a part of the A cations in the crystal lattice. Therefore, the organic ammonium salt compound not only participates in the formation of the perovskite, but also regulates the growth of the perovskite, thereby improving the crystal quality of the perovskite photoactive layer.
[0010] The second object of the present invention is to provide a method for preparing the above-mentioned organic ammonium salt-modified perovskite film, which can be prepared by any one of solution crystallization, vapor phase crystallization, solid-vapor phase crystallization, solid-liquid phase crystallization and solid crystallization. According to the present invention, the method for preparing the organic ammonium salt-modified perovskite film comprises:
[0011] (1) dissolving components including lead iodide (PbI2), cesium iodide (CsI), and an organic ammonium salt compound in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and heating and stirring to obtain a perovskite precursor solution 1;
[0012] (2) dissolving the amine halide in an organic solvent S1 to obtain a perovskite precursor solution 2;
[0013] (3) firstly spin-coating the perovskite precursor solution 1 and performing low-temperature annealing treatment;
[0014] (4) Then, the perovskite precursor solution 2 is spin-coated and subjected to high-temperature annealing to obtain the organic ammonium salt-modified perovskite film.
[0015] According to the present invention, in the method for preparing the organic ammonium salt-modified perovskite film:
[0016] The organic ammonium salt compound is selected from the group consisting of RNH3 + or R1R2R3(NH2) n + At least one of the organic ammonium salt compounds, R is an alkyl chain with 1 to 3 atoms, R1, R2, and R3 are independently alkyl chains with 1 to 3 atoms, and n is an integer of 1 to 3; preferably, the organic ammonium salt compound is selected from CH3NH3 + 、CH3CH2NH3 + 、CH(NH2)2 + 、CH3C(NH2)2 + 、C(NH2)3 + 、(CH3)2NH2 + At least one of the organic ammonium salt compounds, for example, the organic ammonium salt compound can be selected from at least one of guanidine iodide, iodoformamidine, iodoacetamidine, dimethylammonium iodide, and iodoethylamine;
[0017] In the step (1), the dimethyl sulfoxide accounts for 1 to 50 V / V% of the total volume of the mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, preferably 5 to 20 V / V% by volume;
[0018] The cesium iodide is 0.1-10wt% of the lead iodide, and the organic ammonium salt compound is 0.005-20wt% of the lead iodide; preferably, the cesium iodide is 2-8wt% of the lead iodide, and the organic ammonium salt compound is 0.01-5wt% of the lead iodide;
[0019] In the perovskite precursor solution 1, the amount of lead iodide is 1 to 70 wt %, preferably 5 to 60 wt % of the mixed solvent;
[0020] The heating temperature in step (1) is 60 to 200° C., preferably 100 to 160° C.;
[0021] The organic solvent S1 in the perovskite precursor solution 2 is isopropyl alcohol (IPA);
[0022] In the perovskite precursor solution 2, the concentration of the amine halide is 3 to 150 mg / mL, preferably 5 to 120 mg / mL;
[0023] The halogenated amine comprises iodoformamidine (FAI), iodomethylamine (MAI) and chloromethylamine (MACl), preferably, the iodomethylamine is 5-10wt% of the iodoformamidine, and the chloromethylamine is 5-20wt% of the iodoformamidine;
[0024] In the step (3), the conditions for low temperature annealing treatment are: annealing temperature 50-100° C., annealing time 1-5 min;
[0025] In the step (4), the conditions for high temperature annealing treatment are: annealing temperature 120-180° C., annealing time 5-20 min.
[0026] Generally, the main purpose of introducing additives into the precursor is to passivate the defects on the surface and grain boundaries of the perovskite film. The present invention is different from the traditional method. By introducing a small amount of large-sized ammonium salt into the A-site cation, the spatial transfer between multiple cations is realized to achieve the purpose of matching with other elements, thereby improving the lattice energy of the overall perovskite. Compared with the traditional additive method, the advantages of the A-site cation size regulation are mainly manifested in the following two aspects: 1) The spatial transfer of cations of various sizes solves the problem of mismatch between cations and the B and X-site crystal frameworks, thereby improving the [PbI6] 4- 1) The stability of the octahedral framework; 2) It is conducive to the diffusion of the perovskite film formation process and relieves the lattice stress generated during the annealing process; 3) The large-sized ammonium salt not only participates in the formation of the perovskite lattice, but also plays a role in passivating interface defects. No additional additives are required to assist in the formation of high-quality perovskite films, which can be said to kill two birds with one stone. The perovskite film prepared by the A-site cation size control method has large and uniform grain size, so the photoelectric conversion efficiency and stability of the corresponding perovskite solar cell have also been greatly improved.
[0027] The third object of the present invention is to provide a perovskite solar cell, which comprises, in sequence: a cathode electrode, an electron transport layer, a perovskite active layer containing the above-mentioned organic ammonium salt-modified perovskite film or the organic ammonium salt-modified perovskite film obtained by the above-mentioned preparation method, a hole transport layer and a metal electrode. The structure of the perovskite solar cell is cathode / electron transport layer / perovskite active layer / hole transport layer / anode.
[0028] According to the present invention, in the perovskite solar cell:
[0029] The cathode electrode is indium tin oxide;
[0030] The electron transport layer is tin dioxide;
[0031] The thickness of the electron transport layer is 3 to 50 nm, preferably 5 to 30 nm;
[0032] The thickness of the perovskite active layer is 100 to 1500 nm, preferably 150 to 900 nm;
[0033] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) and molybdenum trioxide (MoO3). Preferably, in the hole transport layer, the thickness of Spiro-OMeTAD is 40 to 250 nm, preferably 50 to 200 nm; the thickness of MoO3 is 2 to 20 nm, preferably 2 to 10 nm;
[0034] The metal electrode is silver;
[0035] The thickness of the metal electrode is 40 to 300 nm, preferably 50 to 200 nm.
[0036] The fourth object of the present invention is to provide a method for preparing the above-mentioned perovskite solar cell, comprising: cleaning the surface of the cathode substrate, spin coating the electron transport layer, spin coating the perovskite active layer, preparing the hole transport layer, and evaporating the metal electrode. Specifically, the preparation method comprises the following steps:
[0037] Step 1: Clean, dry and surface treat the cathode substrate to obtain a clean substrate;
[0038] The cleaning, drying and surface treatment of the cathode substrate can all be carried out in a manner commonly used in the art, for example, specifically including: repeatedly scrubbing the ITO surface with absorbent cotton in a detergent solution, then ultrasonically cleaning with detergent, acetone, anhydrous ethanol, and isopropanol for 10 to 20 minutes each twice, and drying in a vacuum drying oven; finally, subjecting the cleaned and dried cathode substrate to an ultraviolet ozone treatment for 10 to 20 minutes;
[0039] Step 2: Preparation of precursor solution:
[0040] (a) Preparation of SnO2 precursor solution:
[0041] Dispersing the SnO2 nanoparticle colloidal solution in water to obtain a SnO2 precursor solution;
[0042] (b) Preparation of perovskite precursor solution:
[0043] Dissolving components including lead iodide, cesium iodide and an organic ammonium salt compound in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and heating and stirring to obtain a perovskite precursor solution 1; the heating temperature is not particularly limited, and the lead iodide, cesium iodide and the organic ammonium salt compound can be dissolved in the mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide under the heating condition;
[0044] Dissolving the amine halide in an organic solvent S1 to obtain a perovskite precursor solution 2;
[0045] (c) Preparation of hole transport layer solution:
[0046] In a protective gas atmosphere, Spiro-OMeTAD, 4-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in an organic solvent S2 to obtain a hole transport layer solution;
[0047] Step 3: Preparation of SnO2 electron transport layer
[0048] In air, spin-coating the SnO2 precursor solution on the clean substrate obtained in step 1, and after annealing, obtaining a SnO2 electron transport layer;
[0049] Step 4: Preparation of perovskite active layer
[0050] In a protective gas atmosphere, the perovskite precursor solution 1 is spin-coated on the surface of the SnO2 electron transport layer, and annealed at low temperature to obtain an ammonium salt-modified PbI2 film, and then the perovskite precursor solution 2 is spin-coated on the cooled surface of the PbI2 film, and then annealed at high temperature to obtain a perovskite active layer;
[0051] Step 5: Preparation of hole transport layer
[0052] In a protective gas atmosphere, the hole transport layer solution was spin-coated on the cooled perovskite active layer, and then MoO3 was evaporated;
[0053] Step 6: Preparation of metal electrodes
[0054] After evaporating the metal electrode in a coating machine, the perovskite solar cell is obtained.
[0055] According to the present invention, in the method for preparing the perovskite solar cell:
[0056] In the step (a), the amount of SnO2 nanoparticle colloidal solution used is 5 to 30 wt% of water, preferably 10 to 20 wt%;
[0057] In the step (b), the dimethyl sulfoxide accounts for 1 to 50 V / V% of the total volume of the mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, preferably 5 to 20 V / V% by volume;
[0058] The organic ammonium salt compound is selected from the group consisting of RNH3 + or R1R2R3(NH2) n +At least one of the organic ammonium salt compounds, R is an alkyl chain with 1 to 3 atoms, R1, R2, and R3 are independently alkyl chains with 1 to 3 atoms, and n is an integer of 1 to 3; preferably, the organic ammonium salt compound is selected from CH3NH3 + 、CH3CH2NH3 + 、CH(NH2)2 + 、CH3C(NH2)2 + 、C(NH2)3 + 、(CH3)2NH2 + At least one of the organic ammonium salt compounds, for example, the organic ammonium salt compound can be selected from at least one of guanidine iodide, iodoformamidine, iodoacetamidine, dimethylammonium iodide, and iodoethylamine;
[0059] The cesium iodide is 0.1-10wt% of the lead iodide, and the organic ammonium salt compound is 0.005-20wt% of the lead iodide; preferably, the cesium iodide is 2-8wt% of the lead iodide, and the organic ammonium salt compound is 0.01-5wt% of the lead iodide;
[0060] In the perovskite precursor solution 1, the amount of lead iodide is 1 to 70 wt %, preferably 5 to 60 wt % of the mixed solvent;
[0061] The organic solvent S1 in the perovskite precursor solution 2 is isopropyl alcohol (IPA);
[0062] In the perovskite precursor solution 2, the concentration of the amine halide is 3 to 150 mg / mL, preferably 5 to 120 mg / mL;
[0063] The halogenated amine comprises iodoformamidine (FAI), iodomethylamine (MAI) and chloromethylamine (MACl), preferably, the iodomethylamine is 5-10wt% of the iodoformamidine, and the chloromethylamine is 5-20wt% of the iodoformamidine;
[0064] The organic solvent S2 in the hole transport layer solution is chlorobenzene;
[0065] In the hole transport layer solution, the volume percentage of tetra-tert-butylpyridine is 2-3% of the volume of the organic solvent S2, and the volume percentage of lithium bis(trifluoromethanesulfonyl)imide is 1.5-2.5 V / V% of the volume of the organic solvent S2; in the hole transport layer solution, the amount of Spiro-OMeTAD is 60-120 mg per mL of organic solvent S2.
[0066] According to the present invention, in the method for preparing the perovskite solar cell:
[0067] The protective gas may be any commonly used protective gas in the art, such as nitrogen;
[0068] In the step 1, the cathode substrate surface is treated by ultraviolet ozone treatment;
[0069] In the step 3, the spin coating conditions are: a rotation speed of 3000-5000 rpm, and a time of 30-60 seconds; the annealing conditions are: an annealing temperature of 120-180° C., and an annealing time of 30-60 minutes;
[0070] In the step 4, the conditions for low-temperature annealing are: annealing temperature 50-100°C, annealing time 1-5 min; the conditions for high-temperature annealing are: annealing temperature 120-180°C, annealing time 5-20 min;
[0071] In step 5, the spin coating conditions are: a rotation speed of 3000-4000 rpm, a time of 30-60 s; and a MoO3 evaporation condition of less than 2×10 -4 Pa, the rate is
[0072] The metal evaporation condition in step 6 is that the pressure in the evaporation chamber is maintained at 2×10 -4 Pa below Evaporation rate.
[0073] The present invention improves [PbI6] by adjusting the size of the A-site cation 4- The stability of the octahedral framework is improved, thereby improving the photoelectric conversion performance and stability of the solar cell. The goal of the present invention is to solve the problem of low lattice energy and poor stability of perovskite caused by ion radius mismatch. To this end, the present invention introduces a small amount of ammonium salt with a larger radius into the A-site cation to improve the size matching between elements in the lattice through size space transfer. On the one hand, the introduction of ammonium salt can preferentially stabilize [PbI6] 4- The octahedral framework is conducive to the diffusion of the perovskite film formation process, relieves the lattice stress caused by the annealing process, and improves the quality of the perovskite film. On the other hand, the large-radius organic ammonium salt itself can be used as a perovskite component without destroying the perovskite crystal structure. Through this method, a perovskite film with larger grains and better crystallinity can be obtained, the internal defects and grain boundaries of the film can be reduced, and the separation and transmission of carriers can be enhanced, thereby significantly improving the stability and photoelectric conversion efficiency of perovskite solar cells.
[0074] The perovskite solar cell provided by the present invention has the following advantages and gain effects:
[0075] 1. The present invention provides a method for introducing large-sized organic ammonium salt compounds to stabilize the perovskite lattice and obtain a high-performance perovskite solar cell. By introducing large-sized organic ammonium salt compounds into the perovskite precursor PbI2 solution, a perovskite film with large grain size and better crystallinity is prepared, and the defects and grain boundaries of the perovskite film are reduced, thereby improving the photogenerated carrier lifetime and the stability of the device, providing a new method for preparing high-performance and high-stability perovskite solar cells;
[0076] 2. After the introduction of large-sized organic ammonium salt compounds, the performance parameters of perovskite solar cells (including open-circuit voltage, short-circuit current density and fill factor) have been significantly improved, and the highest photoelectric conversion efficiency has reached 23.5%; more importantly, after the unpackaged devices are stored in a nitrogen environment for 3300 hours, they can still maintain more than 96% of the initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 Schematic diagram of the structure of a perovskite solar cell device containing a large-sized organic ammonium salt-modified perovskite active layer in an embodiment of the present invention.
[0078] Figure 2 The current density and voltage relationship curves of the unmodified comparative example 1 (Control) and the perovskite solar cell devices introduced with different large-sized organic ammonium salt compounds in Examples 1 to 3 are shown in Figures 1, 2 and 3, respectively, are the current density and voltage relationship curves of the perovskite solar cell devices prepared in Examples 1 to 3, with the horizontal axis being the voltage (V) and the vertical axis being the current density J sc (mA cm -2 ).
[0079] FIG3 is a scanning electron microscope image of the perovskite film prepared in Comparative Example 1 and Examples 1 to 3, wherein Figure 3a This is the morphology of the perovskite film in Comparative Example 1 without adding ammonium salt. Figure 3b ~d are the morphology pictures of the perovskite films modified with organic ammonium salts in Examples 1 to 3, respectively.
[0080] Figure 4 Curves showing changes in photoelectric conversion efficiency over time for the perovskite solar cell device of Comparative Example 1 (curve 1) and the perovskite solar cell device of Example 4 introducing a large-sized organic ammonium salt compound (curve 2) under a nitrogen environment, wherein the horizontal axis is time (h) and the vertical axis is photoelectric conversion rate PCE (%). DETAILED DESCRIPTION
[0081] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0082] The test instruments and test conditions used in the examples are as follows:
[0083] JV curve: The whole test was conducted in a N2 glove box. The solar simulator used was the SS-F5-3A solar simulator from Optimax Technology. First, a standard silicon solar cell (2×2cm 2 , SRC-00019) calibrated to the standard solar spectrum corresponding to 1 sun (AM 1.5G, 100mW / cm 2 ) The device is then placed under the calibrated test light source using a 3M test fixture, and the JV characteristic curve is automatically tested using a Keithley 2450 source meter and the corresponding software. The open-circuit voltage (V oc ), short-circuit current density (Short-circuit density, J sc ), fill factor (FF) and power conversion efficiency (PCE). Set the test voltage to -0.2V to 1.2V, the interval to 0.02V, and the delay time to 0.1s.
[0084] SEM image: Hitachi SU8010 ultra-high resolution scanning / scanning transmission electron microscope.
[0085] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0086] Comparative Example 1
[0087] The structure of the perovskite solar cell device in this comparative example without the addition of large-sized ammonium salt compounds to stabilize the perovskite lattice is: ITO / SnO2 / FA 1-x MA x PbI3 / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0088] (1) In a detergent solution, the ITO surface is repeatedly scrubbed with cotton, and then ultrasonically cleaned with detergent, acetone, anhydrous ethanol, and isopropanol for 20 minutes each twice, and dried in a vacuum drying oven for 15 minutes; finally, the cleaned and dried cathode substrate is treated with ultraviolet ozone (UVO) for 20 minutes. The purpose of UVO treatment is to remove residual organic matter on the ITO surface and increase wettability.
[0089] (2) The SnO2 nanoparticle colloidal solution and ultrapure water are diluted in a volume ratio of 1:5, ultrasonically dispersed for 30 minutes, and the diluted SnO2 nanoparticle solution is spin-coated on the ITO surface treated in step (1) at a speed of 4000 rpm for 30 seconds; then annealing is performed at a temperature of 150°C for 60 minutes to obtain a SnO2 electron transport layer with a thickness of 15 nm.
[0090] (3) Spin-coat the perovskite active layer solution on the surface of the above electron transport layer in two steps: first, dissolve 650 mg of PbI2 in 1 mL of a mixed solvent of DMF and DMSO with a volume ratio of 90:10, and heat and stir at 70°C overnight; dissolve FAI, MAI, and MACl in 1 mL of IPA solvent at a mass ratio of 90 mg:6.4 mg:9 mg, and stir overnight. Filter with a polytetrafluoroethylene filter with a pore size of 0.45 μm to obtain PbI2 precursor solution 1 and FAI precursor solution 2; spin-coat the surface of the SnO2 electron transport layer with precursor solution 1, and then anneal at 70°C for 1 min; then spin-coat precursor solution 2 on the cooled surface of the PbI2 film, and anneal at 150°C for 10 min to obtain an unmodified perovskite active layer with a thickness of 800 nm.
[0091] (4) Preparation of hole transport layer Spiro-OMeTAD and MoO3 on the perovskite active layer: The preparation process of Spiro-OMeTAD is as follows: 73 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and 30 μL of TBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI solution (520 mg / mL lithium bis(trifluoromethanesulfonyl)imide in acetonitrile) are added. The solution is spin-coated on the perovskite active layer at a speed of 3000 rpm / 30 s / time to a thickness of 180 nm. The hole transport layer MoO3 is evaporated on the surface of the above Spiro-OMeTAD, and the vacuum degree is less than 2×10 -4 Pa, the rate is The thickness is 8nm.
[0092] (5) Deposit the anode layer Ag on the surface of the hole transport layer: -6 mbar, Ag was evaporated at a rate of 80 nm to obtain a perovskite solar cell device without the introduction of large-sized ammonium salt: ITO / SnO2 / FA 1-x MA x PbI3 / Spiro-OMeTAD / MoO3 / Ag.
[0093] Example 1
[0094] The structure of a perovskite solar cell device in this embodiment that introduces a large-sized organic ammonium salt compound (guanidine iodide: GAI) to stabilize the perovskite lattice is: ITO / SnO2 / FA 1-x-y MA x GA y PbI3 / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0095] (1) In a detergent solution, the ITO surface is repeatedly scrubbed with cotton, and then ultrasonically cleaned with detergent, acetone, anhydrous ethanol, and isopropanol for 20 minutes each twice, and dried in a vacuum drying oven for 15 minutes; finally, the cleaned and dried cathode substrate is treated with ultraviolet ozone (UVO) for 20 minutes. The purpose of UVO treatment is to remove residual organic matter on the ITO surface and increase wettability.
[0096] (2) The SnO2 nanoparticle colloidal solution and ultrapure water are diluted in a volume ratio of 1:5, ultrasonically dispersed for 30 minutes, and the diluted SnO2 nanoparticle solution is spin-coated on the ITO surface treated in step (1) at a speed of 4000 rpm for 30 seconds; then annealing is performed at a temperature of 150°C for 60 minutes to obtain a SnO2 electron transport layer with a thickness of 15 nm.
[0097] (3) Spin-coat the perovskite active layer solution on the surface of the above electron transport layer in two steps: first, dissolve 600mg PbI2, 14mg CsI and 2mg GAI in 1mL of a mixed solvent of DMF and DMSO with a volume ratio of 90:10, and heat and stir at 70℃ overnight; FAI, MAI, and MACl are dissolved in 1mL of IPA solvent at a mass ratio of 90mg:6.5mg:9mg, and stir overnight. Use a polytetrafluoroethylene filter with a pore size of 0.45μm to filter respectively to obtain PbI2 precursor solution 1 and FAI precursor solution 2; spin-coat the surface of the SnO2 electron transport layer with precursor solution 1, and then anneal at 70℃ for 1min; then spin-coat precursor solution 2 on the cooled surface of the PbI2 film, and anneal at 150℃ for 10min to obtain a GAI-modified perovskite active layer with a thickness of 780nm.
[0098] (4) Preparation of hole transport layer Spiro-OMeTAD and MoO3 on the perovskite active layer: The preparation process of Spiro-OMeTAD is as follows: 73 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and 30 μL of TBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI solution (520 mg / mL lithium bis(trifluoromethanesulfonyl)imide in acetonitrile) are added. The solution is spin-coated on the perovskite active layer at a speed of 3000 rpm / 30 s / time, with a thickness of 185 nm. The hole transport layer MoO3 is evaporated on the surface of the above Spiro-OMeTAD, and the vacuum degree is less than 2×10 -4 Pa, the rate is The thickness is 8nm.
[0099] (5) Deposit the anode layer Ag on the surface of the hole transport layer: -6 mbar, Ag was evaporated at a rate of 100 nm to obtain a perovskite solar cell device with a large-sized ammonium salt compound GAI stabilized perovskite lattice: ITO / SnO2 / FA 1-x-y MA x GA y PbI3 / Spiro-OMeTAD / MoO3 / Ag.
[0100] Figure 2 The current density and voltage relationship curves of the perovskite solar cell device introduced with the large-sized ammonium salt compound in Comparative Example 1 and Example 1 of the present invention are shown in FIG. 1 . Curve 1 is the perovskite solar cell device introduced with the large-sized ammonium salt GAI, and its open circuit voltage (V oc ) is 1.161V, the short-circuit current (J sc ) is 24.36 mA / cm 2 , the fill factor (FF) is 81.85%; while the perovskite solar cell of comparative example 1 has a V oc is 1.105V, J sc 23.89mA / cm 2 , FF is 78.20%, which shows that the introduction of large-sized ammonium salt compounds can effectively reduce the internal defects of perovskite, enhance the carrier separation efficiency and transmission efficiency, and ultimately improve the photoelectric performance of the device.
[0101] Figure 3(b) is a morphology of the perovskite film with the large-sized ammonium salt compound GAI introduced in this embodiment. The figure shows that after the introduction of GAI, the holes in the perovskite film are reduced and the grains are significantly larger, thereby improving the quality of the perovskite film.
[0102] The photoelectric performance comparison between the perovskite solar cell device with large-sized ammonium salt compounds introduced in the embodiment of the present invention and the unmodified perovskite solar cell device is shown in Table 1:
[0103] Table 1
[0104] ETL <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF(%) PCE(%) Comparative Example 1 1.105 23.89 78.20 20.65 Example 1 1.169 24.83 81.10 23.55 Example 2 1.156 24.10 79.87 22.24 Example 3 1.128 24.84 79.99 22.41
[0105] From Table 1, it can be found that V oc The voltage increased from 1.105V to 1.169V, the FF increased from 78.20% to 81.10%, and the photoelectric conversion efficiency (PCE) increased from 20.65% to 23.55%. This shows that the introduction of GAI can stabilize the perovskite crystal structure, enhance the crystallization of perovskite films, reduce defects, and significantly improve the photoelectric performance of the device.
[0106] Example 2
[0107] The structure of a perovskite solar cell device in this embodiment that introduces a large-sized ammonium salt compound (iodine formamidine: FAI) to stabilize the perovskite lattice is: ITO / SnO2 / FA 1-x MA x PbI3 / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0108] (1) In a detergent solution, the ITO surface is repeatedly scrubbed with cotton, and then ultrasonically cleaned with detergent, acetone, anhydrous ethanol, and isopropanol for 20 minutes each twice, and dried in a vacuum drying oven for 15 minutes; finally, the cleaned and dried cathode substrate is treated with ultraviolet ozone (UVO) for 20 minutes. The purpose of UVO treatment is to remove residual organic matter on the ITO surface and increase wettability.
[0109] (2) The SnO2 nanoparticle colloidal solution and ultrapure water are diluted in a volume ratio of 1:5, ultrasonically dispersed for 30 minutes, and the diluted SnO2 nanoparticle solution is spin-coated on the ITO surface treated in step (1) at a speed of 4000 rpm for 30 seconds; then annealing is performed at a temperature of 180°C for 60 minutes to obtain a SnO2 electron transport layer with a thickness of 15 nm.
[0110] (3) Spin-coat the perovskite active layer solution on the surface of the above electron transport layer in two steps; first, dissolve 691mg PbI2, 17mg CsI and 2mg FAI in 1mL of a mixed solvent of DMF and DMSO with a volume ratio of 90:5, and heat and stir at 70℃ overnight; FAI, MAI, and MACl are dissolved in 1mL of IPA solvent at a mass ratio of 90mg:9mg:9mg, and stir overnight. Use a polytetrafluoroethylene filter with a pore size of 0.45μm to filter respectively to obtain PbI2 precursor solution 1 and FAI precursor solution 2; spin-coat the surface of the SnO2 electron transport layer with precursor solution 1, and then anneal at 70℃ for 5min; then spin-coat precursor solution 2 on the cooled surface of the PbI2 film, and anneal at 150℃ for 10min to obtain a FAI-modified perovskite active layer with a thickness of 890nm.
[0111] (4) Preparation of hole transport layer Spiro-OMeTAD and MoO3 on the perovskite active layer: The preparation process of Spiro-OMeTAD is as follows: 81 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and 30 μL of TBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI solution (520 mg / mL lithium bis(trifluoromethanesulfonyl)imide in acetonitrile) are added. The solution is spin-coated on the perovskite active layer at a speed of 3500 rpm / 30 s / time, with a thickness of 190 nm. The hole transport layer MoO3 is evaporated on the surface of the above Spiro-OMeTAD, and the vacuum degree is less than 2×10 -4 Pa, the rate is The thickness is 8nm.
[0112] (5) Deposit the anode layer Ag on the surface of the hole transport layer: -6 mbar, Ag was evaporated at a rate of 90 nm to obtain a perovskite solar cell device with a large-sized ammonium salt compound FAI stabilizing the perovskite lattice: ITO / SnO2 / FA 1-x MA x PbI3 / Spiro-OMeTAD / MoO3 / Ag.
[0113] Figure 2 Curve 2 in the middle is the perovskite solar cell device with large-sized ammonium salt FAI introduced in this embodiment, and its open circuit voltage (V oc ) is 1.156V, the short-circuit current (J sc ) is 24.10 mA / cm 2 , the filling factor (FF) is 79.87%; while the perovskite solar cell of comparative example 1 has a V oc is 1.105V, J sc 23.89mA / cm 2, FF is 78.20%. From Table 1, it can be found that the PCE of this embodiment is increased from 20.65% to 22.24%, which shows that the introduction of FAI can stabilize the perovskite crystal structure, enhance the crystallization of the perovskite film, effectively reduce the internal defects of the perovskite, enhance the carrier separation efficiency and transmission efficiency, and finally improve the photoelectric performance of the device.
[0114] Figure 3(c) is a morphology of the perovskite film with the large-sized ammonium salt compound FAI introduced in this embodiment. The figure shows that after the introduction of FAI, the holes in the perovskite film are significantly reduced, and the perovskite film becomes denser, thereby improving the quality of the perovskite film.
[0115] Example 3
[0116] The structure of a perovskite solar cell device in this embodiment that introduces a large-sized ammonium salt compound (dimethylammonium iodide: DMAI) to stabilize the perovskite lattice is: ITO / SnO2 / FA 1-x-y MA x DMA y PbI3 / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0117] (1) In a detergent solution, the ITO surface is repeatedly scrubbed with cotton, and then ultrasonically cleaned with detergent, acetone, anhydrous ethanol, and isopropanol for 20 minutes each twice, and dried in a vacuum drying oven for 15 minutes; finally, the cleaned and dried cathode substrate is treated with ultraviolet ozone for 20 minutes. The purpose of UVO treatment is to remove residual organic matter on the ITO surface and increase wettability.
[0118] (2) The SnO2 nanoparticle colloidal solution and ultrapure water were diluted in a volume ratio of 1:6, and ultrasonically dispersed for 30 minutes. The diluted SnO2 nanoparticle solution was spin-coated on the ITO surface treated in step (1) at a speed of 3000 rpm for 30 seconds. Subsequently, an annealing treatment was performed at a temperature of 180°C for 30 minutes to obtain a SnO2 thin film with a thickness of 15 nm.
[0119] (3) Spin-coat the perovskite active layer solution on the surface of the above electron transport layer in two steps: first, dissolve 650mg PbI2, 14mg CsI and 2mg DMAI in 1mL of a mixed solvent of DMF and DMSO with a volume ratio of 95:5, and heat and stir at 70℃ overnight; FAI, MAI, and MACl are dissolved in 1mL of IPA solvent at a mass ratio of 90mg:7mg:9mg, and stir overnight. Use a polytetrafluoroethylene filter with a pore size of 0.45μm to filter respectively to obtain PbI2 precursor solution 1 and FAI precursor solution 2; spin-coat the surface of the SnO2 electron transport layer with precursor solution 1, and then anneal at 100℃ for 5min; then spin-coat the surface of the cooled PbI2 film with precursor solution 2, and anneal at 150℃ for 10min to obtain a DMAI-modified perovskite active layer with a thickness of 810nm.
[0120] (4) Preparation of hole transport layer Spiro-OMeTAD and MoO3 on the perovskite active layer: The preparation process of Spiro-OMeTAD is as follows: 101 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and 28.8 μL of TBP (tetra-tert-butylpyridine) and 17.5 μL of LiTFSI solution (520 mg / mL lithium bis(trifluoromethanesulfonyl)imide in acetonitrile) are added. The solution is spin-coated on the perovskite layer at a speed of 4000 rpm / 50 s / time to a thickness of 200 nm. The hole transport layer MoO3 is evaporated on the surface of the above Spiro-OMeTAD, and the vacuum degree is less than 2×10 -4 Pa, the rate is The thickness is 8nm.
[0121] (5) Deposit the anode layer Ag on the surface of the hole transport layer: -6 mbar, Ag was evaporated at a rate of 80 nm to obtain a perovskite solar cell device with a large-sized ammonium salt compound DMAI stabilizing the perovskite lattice: ITO / SnO2 / FA 1-x-y MA x DMA y PbI3 / Spiro-OMeTAD / MoO3 / Ag.
[0122] Figure 2 Curve 3 in the middle is the perovskite solar cell device with large-sized ammonium salt FAI introduced in this embodiment, and its open circuit voltage (V oc ) is 1.128V, short-circuit current (J sc ) is 24.84 mA / cm 2 , the filling factor (FF) is 79.99%; while the perovskite solar cell of comparative example 1 has a V oc is 1.105V, J sc23.89mA / cm 2 , FF is 78.20%. From Table 1, it can be found that the PCE of this embodiment is increased from 20.65% to 22.41%, which shows that the introduction of DMAI can stabilize the perovskite crystal structure, enhance the crystallization of the perovskite film, effectively reduce the internal defects of the perovskite, enhance the carrier separation efficiency and transmission efficiency, and finally improve the photoelectric performance of the device.
[0123] Figure 3(d) is a morphology of the perovskite film with the large-sized ammonium salt compound DMAI introduced in this embodiment. The figure shows that after the introduction of DMAI, the holes in the perovskite film are significantly reduced, the perovskite film becomes denser, and the perovskite grains are significantly larger, thereby improving the quality of the perovskite film.
[0124] Example 4
[0125] The structure of a perovskite solar cell device in this embodiment that introduces a large-sized ammonium salt compound (ethyl iodide: EAI) to stabilize the perovskite lattice is: ITO / SnO2 / FA 1-x-y MA x EA y PbI3 / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0126] (1) In a detergent solution, the ITO surface is repeatedly scrubbed with cotton, and then ultrasonically cleaned with detergent, acetone, anhydrous ethanol, and isopropanol for 20 minutes each twice, and dried in a vacuum drying oven for 15 minutes; finally, the cleaned and dried cathode substrate is treated with ultraviolet ozone for 20 minutes. The purpose of UVO treatment is to remove residual organic matter on the ITO surface and increase wettability.
[0127] (2) The SnO2 nanoparticle colloidal solution and ultrapure water were diluted in a volume ratio of 1:6.5, and ultrasonically dispersed for 30 minutes. The diluted SnO2 nanoparticle solution was spin-coated on the ITO surface treated in step (1) at a speed of 3000 rpm for 30 seconds. Subsequently, an annealing treatment was performed at a temperature of 150°C for 30 minutes to obtain a SnO2 thin film with a thickness of 15 nm.
[0128] (3) Spin-coat the perovskite active layer solution on the surface of the above electron transport layer in two steps: first, dissolve 691mg PbI2, 17mg CsI and 5mg EAI in 1mL of a mixed solvent of DMF and DMSO with a volume ratio of 94:6, and heat and stir at 70℃ overnight; FAI, MAI, and MACl are dissolved in 1mL of IPA solvent at a mass ratio of 90mg:9mg:9mg, and stir overnight. Use a polytetrafluoroethylene filter with a pore size of 0.45μm to filter respectively to obtain PbI2 precursor solution 1 and FAI precursor solution 2; spin-coat the surface of the SnO2 electron transport layer with precursor solution 1, and then anneal at 100℃ for 1min; then spin-coat precursor solution 2 on the cooled surface of the PbI2 film, anneal at 150℃ for 15min, and obtain an EAI-modified perovskite active layer with a thickness of 880nm.
[0129] (4) Preparation of hole transport layer Spiro-OMeTAD and MoO3 on the perovskite active layer: The preparation process of Spiro-OMeTAD is as follows: 92 mg of Spiro-OMeTAD is dissolved in 1 mL of chlorobenzene, and 30 μL of TBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI solution (520 mg / mL lithium bis(trifluoromethanesulfonyl)imide in acetonitrile) are added. The solution is spin-coated on the perovskite active layer at a speed of 4000 rpm / 40 s / time, with a thickness of 195 nm. The hole transport layer MoO3 is evaporated on the surface of the above Spiro-OMeTAD, and the vacuum degree is less than 2×10 -4 Pa, the rate is The thickness is 8nm.
[0130] (5) Deposit the anode layer Ag on the surface of the hole transport layer: -6 mbar, Ag was evaporated at a rate of 95 nm to obtain a perovskite solar cell device with a large-sized ammonium salt compound EAI stabilized perovskite lattice: ITO / SnO2 / FA 1-x-y MA x EA y PbI3 / Spiro-OMeTAD / MoO3 / Ag.
[0131] Figure 4 Curve 2 is a graph showing the photoelectric conversion efficiency attenuation of the perovskite solar cell device in a nitrogen environment that introduces a large-sized ammonium salt compound EAI in this embodiment. Compared with the perovskite solar cell in Comparative Example 1 (curve 1) that maintains an initial efficiency of 70.6%, after 3300 hours, the efficiency of the device that introduces EAI can still maintain 96.3% of the initial efficiency. This is due to the significant improvement in the quality of the perovskite film after the introduction of EAI, which reduces defects and grain boundaries, enhances the separation and transmission of carriers, and thus greatly improves the stability of the perovskite solar cell.
[0132] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. An organic ammonium salt-modified perovskite film comprising [PbI6] stabilized by organic ammonium cations 4- Structure, the organic ammonium cation is RNH3 + or R1R2R3(NH2) n + The invention relates to an organic ammonium cation with a large radius, R is an alkyl chain having 1 to 3 atoms, R1, R2, and R3 are each independently an alkyl chain having 1 to 3 atoms, and n is an integer of 1 to 3.
2. The perovskite film according to claim 1, characterized in that The radius of the organic ammonium cation is greater than 250 pm, preferably 250 to 400 pm; and / or, The organic ammonium cation is selected from CH3NH3 + 、CH3CH2NH3 + 、CH(NH2)2 + 、CH3C(NH2)2 + 、C(NH2)3 + 、(CH3)2NH2 + At least one of .
3. The perovskite thin film according to claim 1 or 2, characterized in that: The organic ammonium cation is [PbI6] 4- 0.005 to 20 wt%, preferably 0.01 to 5 wt%.
4. A method for preparing the organic ammonium salt-modified perovskite film according to any one of claims 1 to 3, comprising: (1) dissolving components including lead iodide, cesium iodide, and an organic ammonium salt compound in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and heating and stirring to obtain a perovskite precursor solution 1; (2) dissolving the amine halide in an organic solvent S1 to obtain a perovskite precursor solution 2; (3) firstly spin-coating the perovskite precursor solution 1 and performing low-temperature annealing treatment; (4) Then, the perovskite precursor solution 2 is spin-coated and subjected to high-temperature annealing to obtain the organic ammonium salt-modified perovskite film.
5. The preparation method according to claim 4, characterized in that: The organic ammonium salt compound is selected from the group consisting of RNH3 + or R1R2R3(NH2) n + At least one of the organic ammonium salt compounds, R is an alkyl chain with 1 to 3 atoms, R1, R2, and R3 are independently alkyl chains with 1 to 3 atoms, and n is an integer of 1 to 3; preferably, the organic ammonium salt compound is selected from CH3NH3 + 、CH3CH2NH3 + 、CH(NH2)2 + 、CH3C(NH2)2 + 、C(NH2)3 + 、(CH3)2NH2 + At least one of the organic ammonium salt compounds; and / or, In the step (1), the dimethyl sulfoxide accounts for 1 to 50 V / V% of the total volume of the mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, preferably 5 to 20 V / V% by volume; and / or, The cesium iodide is 0.1-10wt% of the lead iodide, and the organic ammonium salt compound is 0.005-20wt% of the lead iodide; preferably, the cesium iodide is 2-8wt% of the lead iodide, and the organic ammonium salt compound is 0.01-5wt% of the lead iodide; and / or, In the perovskite precursor solution 1, the amount of lead iodide used is 1 to 70 wt%, preferably 5 to 60 wt% of the mixed solvent; and / or, The heating temperature in step (1) is 60 to 200° C., preferably 100 to 160° C.; and / or, The organic solvent S1 in the perovskite precursor solution 2 is isopropanol; and / or, In the perovskite precursor solution 2, the concentration of the amine halide is 3 to 150 mg / mL, preferably 5 to 120 mg / mL; and / or, The halogenated amine comprises iodoformamidine, iodomethylamine and chloromethylamine, preferably, the iodomethylamine is 5-10wt% of the iodoformamidine, and the chloromethylamine is 5-20wt% of the iodoformamidine; and / or, In the step (3), the conditions for low temperature annealing treatment are: annealing temperature 50-100° C., annealing time 1-5 min; and / or, In the step (4), the conditions for high temperature annealing treatment are: annealing temperature 120-180° C., annealing time 5-20 min.
6. A perovskite solar cell, comprising: A cathode electrode, an electron transport layer, a perovskite active layer comprising a perovskite film modified with an organic ammonium salt as claimed in any one of claims 1 to 3 or a perovskite film modified with an organic ammonium salt obtained by the preparation method as claimed in claim 4 or 5, a hole transport layer and a metal electrode.
7. The perovskite solar cell according to claim 6, characterized in that: The cathode electrode is indium tin oxide; and / or, The electron transport layer is tin dioxide; and / or, The thickness of the electron transport layer is 3 to 50 nm, preferably 5 to 30 nm; and / or, The thickness of the perovskite active layer is 100 to 1500 nm, preferably 150 to 900 nm; and / or, The hole transport layer is Spiro-OMeTAD and molybdenum trioxide. Preferably, in the hole transport layer, the thickness of Spiro-OMeTAD is 40 to 250 nm, preferably 50 to 200 nm; the thickness of molybdenum trioxide is 2 to 20 nm, preferably 2 to 10 nm; and / or, The metal electrode is silver; and / or, The thickness of the metal electrode is 40 to 300 nm, preferably 50 to 200 nm.
8. A method for preparing the perovskite solar cell according to claim 6 or 7, comprising: Clean the cathode substrate surface, spin-coat the electron transport layer, spin-coat the perovskite active layer, prepare the hole transport layer, and evaporate the metal electrode.
9. The preparation method according to claim 8, characterized in that: The preparation method specifically comprises the following steps: Step 1: Clean, dry and surface treat the cathode substrate to obtain a clean substrate; Step 2: Preparation of precursor solution: (a) Preparation of SnO2 precursor solution: Dispersing the SnO2 nanoparticle colloidal solution in water to obtain a SnO2 precursor solution; (b) Preparation of perovskite precursor solution: Dissolving components including lead iodide, cesium iodide and an organic ammonium salt compound in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and heating and stirring to obtain a perovskite precursor solution 1; Dissolving the amine halide in an organic solvent S1 to obtain a perovskite precursor solution 2; (c) Preparation of hole transport layer solution: In a protective gas atmosphere, Spiro-OMeTAD, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonyl)imide are dissolved in an organic solvent S2 to obtain a hole transport layer solution; Step 3: Preparation of SnO2 electron transport layer In air, spin-coating the SnO2 precursor solution on the clean substrate obtained in step 1, and after annealing, obtaining a SnO2 electron transport layer; Step 4: Preparation of perovskite active layer In a protective gas atmosphere, the perovskite precursor solution 1 is spin-coated on the surface of the SnO2 electron transport layer, and annealed at low temperature to obtain an ammonium salt-modified PbI2 film, and then the perovskite precursor solution 2 is spin-coated on the cooled surface of the PbI2 film, and then annealed at high temperature to obtain a perovskite active layer; Step 5: Preparation of hole transport layer In a protective gas atmosphere, the hole transport layer solution was spin-coated on the cooled perovskite active layer, and then MoO3 was evaporated; Step 6: Preparation of metal electrodes After evaporating the metal electrode in a coating machine, the perovskite solar cell is obtained.
10. The preparation method according to claim 9, characterized in that: In the step (a), the amount of SnO2 nanoparticle colloidal solution used is 5 to 30 wt % of water, preferably 10 to 20 wt %; and / or, In the step (b), the dimethyl sulfoxide accounts for 1 to 50 V / V% of the total volume of the mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, preferably 5 to 20 V / V% by volume; and / or, The organic ammonium salt compound is selected from the group consisting of RNH3 + or R1R2R3(NH2) n + At least one of the organic ammonium salt compounds, R is an alkyl chain with 1 to 3 atoms, R1, R2, and R3 are independently alkyl chains with 1 to 3 atoms, and n is an integer of 1 to 3; preferably, the organic ammonium salt compound is selected from CH3NH3 + 、CH3CH2NH3 + 、CH(NH2)2 + 、CH3C(NH2)2 + 、C(NH2)3 + 、(CH3)2NH2 + At least one of the organic ammonium salt compounds; and / or, The cesium iodide is 0.1-10wt% of the lead iodide, and the organic ammonium salt compound is 0.005-20wt% of the lead iodide; preferably, the cesium iodide is 2-8wt% of the lead iodide, and the organic ammonium salt compound is 0.01-5wt% of the lead iodide; and / or, In the perovskite precursor solution 1, the amount of lead iodide is 1 to 70 wt%, preferably 5 to 60 wt% of the mixed solvent; and / or, The organic solvent S1 in the perovskite precursor solution 2 is isopropanol; and / or, In the perovskite precursor solution 2, the concentration of the amine halide is 3 to 150 mg / mL, preferably 5 to 120 mg / mL; and / or, The halogenated amine comprises iodoformamidine, iodomethylamine and chloromethylamine, preferably, the iodomethylamine is 5-10wt% of the iodoformamidine, and the chloromethylamine is 5-20wt% of the iodoformamidine; and / or, The organic solvent S2 in the hole transport layer solution is chlorobenzene; and / or, In the hole transport layer solution, the volume percentage of tetra-tert-butylpyridine is 2-3% of the volume percentage of the organic solvent S2, and the volume percentage of lithium bis(trifluoromethanesulfonyl)imide is 1.5-2.5 V / V% of the volume percentage of the organic solvent S2; and / or, In the hole transport layer solution, the amount of Spiro-OMeTAD used is 60-120 mg per mL of organic solvent S2.
11. The preparation method according to claim 9, characterized in that: In the step 1, the cathode substrate surface is treated by ultraviolet ozone treatment; and / or, In the step 3, the spin coating conditions are: a rotation speed of 3000-5000 rpm, and a time of 30-60 seconds; and / or, the annealing conditions are: an annealing temperature of 120-180° C., and an annealing time of 30-60 minutes; and / or, In the step 4, the conditions for low temperature annealing treatment are: annealing temperature 50-100° C., annealing time 1-5 min; and / or, the conditions for high temperature annealing treatment are: annealing temperature 120-180° C., annealing time 5-20 min; and / or, In step 5, the spin coating conditions are: a rotation speed of 3000-4000 rpm, a time of 30-60 s; and / or, the evaporation conditions of MoO3 are less than 2×10 -4 Pa, the rate is and / or, The metal evaporation condition in step 6 is that the pressure in the evaporation chamber is maintained at 2×10 -4 Pa below The rate of evaporation.